(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: In recent times, blockchain technology has emerged as revolutionary technology in various fields, especially in financial and capital markets. The main objective of this research is to analyze the changes in efficiency due to the mathematical concepts of how to improve the performance of the stock market. Three main mathematical models have been used in this study - Market Efficiency Model (Market Efficiancy Model), cost difference models (Cost Differential Model), and risk display models (Risk Exposure Model). These models consider the proportion of transactions, instability, duration of transaction and the relationship between the traditional and blockchain-based system. To support these theories, realistic projects in India and internationally have been included. In India, the background of the National Stock Exchange Blockchain Sandbox Project, CDSL's registration management, and the Reserve Bank of India has been investigated by the background of bond transactions. It has also studied international activities like Nasdaq Linq, Australian Securities Exchange (ASX) and JP Morgan Onyx International activities like this have been studied. In addition, blockchain limits have also been thoroughly analyzed-for example, scalability problems, energy consumption (especially in proof -of-work systems), errors in smart contracts, legal uncertainty and technical complications in combination with conventional systems. These problems have been considered theoretically (such as quaching theory, energy consumption models, game theory, etc.).